Feeding cull beef cows in feedlots - Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
I conducted two trails during 1977 using 115 cows culled from KSU cow herds. Dry cows on lush brome grass gained 1.5 pounds per head per day. Those on a 60% concentrate ration average 2.2 pounds/day; those on 80% concentrate ration, 3.7 pounds/hd/day. The cull, dry cows ate between 23 and 30 pounds of dry matter/day. Cows fed during the Dec. 15-Feb. 15 trial required 2.5 lbs. more dry matter per pound of gain than cows fed during the May 17-June 21 trial. Fastest and most efficient gains were from the 80% concentrate rations. Length of feeding period should coincide with optimum slaughter weight. Results of these trials showed optimum slaughter weight was obtained when a cow weight 22 pounds per inch of height at the withers.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Cull cows; Feedlots